Passive Filter Design for Improving Quality of Solar Power - Ali, Nurhalim Dani; Lysbetti M, Noveri; Firdaus, Firdaus; Amri, Rahyul; Ervianto, Edy (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2018)
With the progress of industry, power electronic equipment is widely used in power system, it has produced serious harmonic distortion. It goes without saying that harmonic analysis is a very important subject in power system. The influence of harmonics dominant because it is permanent. This harmonic influence spread to energy systems, energy devices, and influential to the energy source. For that, it is necessary a tool that is able to overcome these problems so that the electric energy services are not compromised and the reliability was not reduced. This study how to harmonic analysis, total harmonic distortion, and identifying the inverter at a solar power plant 320WP in accordance with the IEEE 519-2014.